Abuso do poder econômico e propriedade intelectual em mercados de alta tecnologia: interface entre concorrência e inovação no acesso a tecnologias e standards - Lima, Felipe Carvalho Eleutério de (2025)
The modern economy is the scene of intense technological change, usually linked to intellectual property, which is constantly reshaping competitive relations between economic agents. In this scenario, the exclusivity and prerogatives conferred by intellectual property raise profound questions regarding the protection of free competition. The interface between competition law and intellectual property law, especially in high-tech markets, is not only the subject of theoretical reflection but also of practical debate. Intellectual property stimulates competition, innovation, and development, but the abuse of economic power associated with intellectual property can jeopardize these phenomena by distorting the merit-based competitive process. Thus, since it is justifiable and appropriate to study the paradigms of legal analysis to address these practical challenges, the objective of the present study is to analyze the intersection between the aforementioned legal regimes, including considerations on the dynamics established between innovation, competition, and development. In order to carry out this study, in terms of methodology, the research is conducted through a critical analysis of the functioning of the legal regimes, considering the legislation, doctrine, and case law relevant to the subject. Finally, based on the study carried out, it was concluded that the legal paradigms of intellectual property and free competition should be considered holistically, with a view to the congruence of the legal system and its ability to optimize innovation and development